2000
DOI: 10.1090/s0002-9947-00-02633-7
|View full text |Cite
|
Sign up to set email alerts
|

Weakly o-minimal structures and real closed fields

Abstract: Abstract. A linearly ordered structure is weakly o-minimal if all of its definable sets in one variable are the union of finitely many convex sets in the structure. Weakly o-minimal structures were introduced by Dickmann, and they arise in several contexts. We here prove several fundamental results about weakly o-minimal structures. Foremost among these, we show that every weakly o-minimal ordered field is real closed. We also develop a substantial theory of definable sets in weakly o-minimal structures, patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
1
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 22 publications
(66 reference statements)
0
107
1
11
Order By: Relevance
“…Let us further mention that as an LV‐structure, R is weakly o‐minimal, i.e., any definable set XR is a finite union of convex definable sets. The paper includes a detailed study of definable sets in such weakly o‐minimal fields and it is shown there that in fact any weakly o‐minimal field must be real closed.…”
Section: Tangent Cones In Real Closed (Valued) Fieldsmentioning
confidence: 99%
“…Let us further mention that as an LV‐structure, R is weakly o‐minimal, i.e., any definable set XR is a finite union of convex definable sets. The paper includes a detailed study of definable sets in such weakly o‐minimal fields and it is shown there that in fact any weakly o‐minimal field must be real closed.…”
Section: Tangent Cones In Real Closed (Valued) Fieldsmentioning
confidence: 99%
“…(It follows that H(M, H) is weakly o-minimal-that is, every unary definable set is a finite union of convex definable sets-but we give a much more detailed statement at the end of this section. See, e.g., Macpherson, Marker and Steinhorn [24] for basic information on weak o-minimality.) .…”
Section: Formentioning
confidence: 99%
“…Therefore, fV is a definable function from open definable set V to M . So, by [, Theorem 4.8] there is an open box BV such that fB is continuous.…”
Section: Prime Models In Weakly O‐minimal Theoriesmentioning
confidence: 99%